TRADISI NIROK NANGGOK SEBAGAI BENTUK KEARIFAN LOKAL MASYARAKAT BELITUNG - Irwandi, Irwandi; Dulkiah, Moh. (JISPO : Jurnal Ilmu Sosial dan Ilmu Politik, 2016)
Nirok Nanggok is a tradition of Belitung people in rural areas conducted during long dry seasons, as rivers and swamps dry up. Nirok Nanggok is a fishing activity using Tirok (a kind of spiky pointed iron spear) and Tanggok (a kind of small net with wooden handle). This activity is usually carried out by one village led by a shaman who led the way the event. Nirok Nanggok is a mass fishing event that is still implemented by the people of Kembiri Village in the Southern part of Belitung Island until now. This event is only held during the long dry season between September and October. This ritual is a form of local wisdom in preserving river ecosystems because fishing is done in rivers that have been determined and regulated by a shaman.